2002
DOI: 10.1148/radiographics.22.suppl_1.g02oc17s3
|View full text |Cite
|
Sign up to set email alerts
|

Combined CT Venography and Pulmonary Angiography: A Comprehensive Review

Abstract: The combination of computed tomographic (CT) venography and pulmonary angiography (CTVPA) was initially described in 1998 as a single comprehensive noninvasive imaging examination for suspected thromboembolic disease. It allowed the identification of pulmonary embolism as well as deep venous thrombosis (DVT) in the abdomen, pelvis, thighs, and calves. The venographic portion of CTVPA has now been studied by multiple researchers and has been shown to be an accurate imaging study for the thigh veins in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 44 publications
0
39
0
8
Order By: Relevance
“…Due to the wide range of reported sensitivity of CT angiography [23][24][25] and the uncertain significance of a missed subsegmental PE, 26 the guideline suggested CTVPA as the imaging modality of choice. 27,28 However, CTVPA was not recommended in patients with renal insufficiency, pregnancy, or allergy to iodinated contrast dye. 6 In such cases, the guideline suggested that the treating physician consult with the radiologist regarding imaging alternatives.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the wide range of reported sensitivity of CT angiography [23][24][25] and the uncertain significance of a missed subsegmental PE, 26 the guideline suggested CTVPA as the imaging modality of choice. 27,28 However, CTVPA was not recommended in patients with renal insufficiency, pregnancy, or allergy to iodinated contrast dye. 6 In such cases, the guideline suggested that the treating physician consult with the radiologist regarding imaging alternatives.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging techniques such as ultrasonography, 151 contrast CT, 152 MRV, and venography are used to confirm the morphological diagnosis of DVT. During lower limb venous ultrasonography (Figure 4), the following four steps of investigation should be performed: (1) determination of the presence/absence of thrombus in lower limb veins; (2) when thrombus is detected, evaluation of its characteristics to stage disease; (3) when acute-phase DVT is present, determination of the extent of thrombus to determine the type of DVT; and (4) examination of the central edge of the thrombus to evaluate it as a potential source of emboli.…”
Section: ) Imaging Techniquesmentioning
confidence: 99%
“…Thrombolysis versus thrombectomy in acute deep vein thrombosis review A practical approach to the management of a patient with acute dVT Just as catheter angiography in the assessment of peripheral vascular disease has largely been replaced by CT or MRI angiography so too has catheter venography been replaced by ultrasound and or CT or MR venography [38][39][40][41].…”
Section: A U T H O R P R O O F Future Science Groupmentioning
confidence: 99%